Analisis Granulometri Batupasir Formasi Tutut di Kecamatan Beutong, Kabupaten Nagan Raya, Provinsi Aceh - Anggi Aulia; Dina Gunarsih; Lia Fitria Rahmatillah; Dewi Sartika; Tika Hapsari; Akmal Muhni (Mataram University, 2026)
This study examines the grain-size distribution of the Tutut Formation sandstone using granulometric analysis. The purpose of this granulometric observation is to determine the depositional environment and its transportation mechanisms. In addition to using granulometric methods, this study also includes geological mapping to observe the rock lithology in the field. The results show that the study location consists of sandstone and mudstone units of the Tutut Formation, Meulaboh sand deposit units, and alluvial deposit units. The characteristics of Tutut Formation sandstone are gray-brown, reddish-brown due to weathering, coarse to fine sand grain size, medium to slightly rounded roundness, and does not react with HCl. Based on granulometric analysis, Tutut Formation sandstone has an average grain size of 0.214-0.327 ϕ, which is classified as coarse sand. The degree of sorting is 0.321 ϕ to 0.417 ϕ, with an average of 0.35 ϕ, so it is classified as good. Skewness values range from 0.107 to 0.263, with an average of 0.1775 ϕ, indicating fine skewness. The 0.1775 ϕ of the average skewness value indicates that the flow in this depositional environment is turbulent and a river depositional environment. Meanwhile, the kurtosis value ranges from 0.060 to 0.11, indicating a platykurtic to highly platykurtic distribution, suggesting a fairly diverse and even grain-size distribution from fine sizes in the matrix to coarse sizes. The diverse grain size implies that the matrix fills the pores between coarse grains. Thus, porosity is not available and has no potential as a reservoir rock.